2017
DOI: 10.1021/acssuschemeng.7b03443
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Aryldiazonium Carbohydrate Coatings: Reduced Adhesion of Foulants at Polymer and Stainless Steel Surfaces in a Marine Environment

Abstract: Surface treatments that minimise biofouling in marine environments are of interest for a variety of applications, such as environmental monitoring and aquaculture. We report on the effect of saccharide coatings on biomass accumulation at the surface of three materials that find applications in marine settings: stainless steel 316 (SS316), nylon-6 (N-6), and poly(ether sulfone) (PES). Saccharides were immobilized via aryldiazonium chemistry; SS316 and N-6 samples were subjected to oxidative surface pre-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…Work from our group has shown that aryldiazonium cations prepared from saccharidebearing aminophenol precursors as in Figure 1 [13], can be used to spontaneously form adlayers of mono-and di-saccharides from solution in a single step. This reaction yields covalent immobilization of glycans on a range of materials including carbon [13][14][15], polymers [16,17], metals and alloys [13,18]; furthermore, it has been extended to more complex glycans that display specific binding interactions with organic substrates, such as cyclodextrins [19].…”
Section: Introductionmentioning
confidence: 99%
“…Work from our group has shown that aryldiazonium cations prepared from saccharidebearing aminophenol precursors as in Figure 1 [13], can be used to spontaneously form adlayers of mono-and di-saccharides from solution in a single step. This reaction yields covalent immobilization of glycans on a range of materials including carbon [13][14][15], polymers [16,17], metals and alloys [13,18]; furthermore, it has been extended to more complex glycans that display specific binding interactions with organic substrates, such as cyclodextrins [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have successfully functionalized COC surfaces in absence of any plasma activation by reducing grafting of aryldiazonium salts via transient formation of the corresponding aryl radicals [16]. Widely used to modify metallic surfaces for their electro-or chemical grafting ability [17][18][19][20], these species also proved to be competent for the functionalization of polymeric surface [21]. From their reduced form, radicals covalently bind to the surface allowing various chemical functions (acids, nitro or bromo groups) to be introduced on the COC surface [16].…”
Section: Introductionmentioning
confidence: 99%
“…The ban of TBT-SPC paints has raised the importance of examining and omitting the environment toxicity of different antifouling coatings before using it in real industrial applications. Different types of antifouling coatings were developed, such as foul release coating [3] , zwitterionic polymers [14][15][16], enzyme [7,17,18] and bioinspired superhydrophobic surfaces [19][20][21][22] that possess low surface energy and hierarchical structure. Additionally, natural compounds such as the essential oils were found to have significant antimicrobial function [23].…”
Section: List Of Tablesmentioning
confidence: 99%
“…Subsequently, the performance of carbohydrates immobilized fouling resistant coatings in the marine environment were studied on three different substrates: stainless steel, nylon and PES. According to the field test results in a coastal environment for 20 days, the carbohydrate coatings show good promise as an environmentally friendly solution for reducing adhesion and retention of marine foulants [22].…”
Section: Surface Chemistrymentioning
confidence: 99%
See 1 more Smart Citation